2022
DOI: 10.1038/s41746-022-00667-w
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic and triage accuracy of digital and online symptom checker tools: a systematic review

Abstract: Digital and online symptom checkers are an increasingly adopted class of health technologies that enable patients to input their symptoms and biodata to produce a set of likely diagnoses and associated triage advice. However, concerns regarding the accuracy and safety of these symptom checkers have been raised. This systematic review evaluates the accuracy of symptom checkers in providing diagnoses and appropriate triage advice. MEDLINE and Web of Science were searched for studies that used either real or simu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
80
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(81 citation statements)
references
References 35 publications
1
80
0
Order By: Relevance
“…7,24,[29][30][31] The most recent review of Wallace et al including 10 studies exhibited an overall primary diagnostic accuracy ranging only from 19% to 38% and from 33% to 58% for the top 3 diagnose. 32 These systematic reviews together with the findings of our study show, that physicians vastly outperformed computerized algorithm-based diagnostic tools, thus, remaining the gold standard for clinical decision-making. However, despite physicians' superior performance, they still provide inaccurate diagnoses in approximately 20% of cases, similar to prior estimated diagnostic error rates of physicians (10%-15%).…”
Section: Discussionsupporting
confidence: 58%
“…7,24,[29][30][31] The most recent review of Wallace et al including 10 studies exhibited an overall primary diagnostic accuracy ranging only from 19% to 38% and from 33% to 58% for the top 3 diagnose. 32 These systematic reviews together with the findings of our study show, that physicians vastly outperformed computerized algorithm-based diagnostic tools, thus, remaining the gold standard for clinical decision-making. However, despite physicians' superior performance, they still provide inaccurate diagnoses in approximately 20% of cases, similar to prior estimated diagnostic error rates of physicians (10%-15%).…”
Section: Discussionsupporting
confidence: 58%
“…Conversely, others mention that it is not clear if the increase in demand of services observed may be due to the emergence of an unmet need or a supply-induced demand [ 56 ]. A specific study to test the impact of WW in decreasing demand and improving efficiency in healthcare resource use in a large real-life study, as suggested by some authors [ 57 ], is already planned.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence was assessed as being mostly weak and insufficient to determine the level of safety of digital and online symptom checkers for patients. More recently, Wallace et al [7] published a systematic review on the diagnostic and triage accuracy of OSCs, including speciality-specific tools but searching only Medline and Web of Science up to 15 February 2021. Both triage and diagnostic accuracy of OSCs were found to be mostly low despite variations.…”
Section: Comparison With Prior Workmentioning
confidence: 99%
“…If inadequately designed, they could misdiagnose and/or misdirect users potentially diverting the user from seeking adequate care or conversely placing additional strain on health systems. Two systematic reviews assessed the literature evaluating OSCs [7,8] with mostly weak evidence regarding their diagnostic and triage accuracy. One review focused only on urgent health issues, while the other included speciality-specific OSCs, and both were outdated following the recent publication of several eligible studies.…”
Section: Introductionmentioning
confidence: 99%